Optimization of turning parameters using ant colony optimization - Mohamad Nazri, Semoin (2008)
This project proposed a new optimization technique based on the ant colony algorithm for solving single-pass turning optimization problems. The cutting process has focus on roughing stages. There are enough handbooks to provide recommended cutting parameters and not consider the economic aspects of machining. The cost of machining on these machines is sensitive to the machining variable. The project objectives are to develop Ant Colony Optimization (ACO) algorithm for CNC turning process and to optimize turning parameters for minimized production cost per unit. Method used for this project is Ant Colony Optimization. This method consists of many steps will elaborate detail in this thesis. The machining parameters are determined by minimized production cost per unit, subject to various practical machining constraints. The results indicate that the proposed ant colony framework is effective to optimized turning parameter. Lastly, ACO algorithm was successfully optimize depth of cut, cutting speed, feed rate and minimized production cost per unit.